2018
DOI: 10.1002/ps.5227
|View full text |Cite
|
Sign up to set email alerts
|

Truck‐mounted area‐wide applications of larvicides and adulticides for extended suppression of adult Aedes albopictus

Abstract: BACKGROUND Given the lack of vaccines for most vector‐borne diseases, vector control is often the primary option for disease control. Aedes albopictus are difficult to control because the immatures primarily develop in containers ubiquitous in residential properties. Conventional adulticide campaigns often result in brief, rebounding population declines, so incorporating new techniques into an integrated pest management program is imperative. We performed combined area‐wide applications of the larvicides Bacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…albopictus populations found that while adulticiding alone has short-lived effects, a combination of adulticiding and larviciding demonstrated extended control of Ae. albopictus populations (Unlu et al 2018). The ability of ground application of Bti by ULV sprayer to treat an entire neighborhood containing Ae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…albopictus populations found that while adulticiding alone has short-lived effects, a combination of adulticiding and larviciding demonstrated extended control of Ae. albopictus populations (Unlu et al 2018). The ability of ground application of Bti by ULV sprayer to treat an entire neighborhood containing Ae.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti population, but it was not cost effective to treat these smaller neighborhoods with a helicopter. Previous studies found that WALS ground applications of Bti were effective at targeting invasive Aedes larvae in domestic containers (Jacups et al 2013, Williams et al 2014, Unlu et al 2018, Garcia-Luna et al 2019, Harris et al 2020, McAllister et al 2020. Based on the published success of WALS, a study was designed to assess the effectiveness of applying VectoBac WDG with a trailer-mounted ULV sprayer in the Florida Keys.…”
Section: Introductionmentioning
confidence: 99%
“…Ultralow-volume (ULV) ground spray application with truck-mounted sprayers has been used for adult control in preventive actions or during dengue outbreaks. Studies have shown that area-wide ULV applications of larvicides could be an effective method to control used tires in certain urban areas (Lucia et al, 2009;Jacups et al, 2013;Doud et al, 2014;Unlu et al, 2019;Burtis et al, 2022). On the other hand, thermal fogging is a method that generates ultra-fine droplets (1-50μm), driving the particles deep inside tiny cracks, crevices, and pores of surfaces or different types of containers.…”
Section: Product Application and Limitationsmentioning
confidence: 99%
“…• Use of PPF ultra low volume, thermal fogging, and fumigant technologies (15 studies) [67][68][69][70][71][72][73][74][75][76][77][78][79][80];…”
Section: Study Characteristicsmentioning
confidence: 99%
“…More recently, studies in Thailand and the USA have shown that multiple spraying machines using combinations of insecticides including PPF were unable to achieve high mortality among Aedes mosquitoes placed in hidden (protected) cages, and that the ULV sprays provided better emergence inhibition than the thermal foggers likely due to larger droplet size [70][71][72].…”
Section: Use Of Ppf Ultra-low Volume Spray Thermal Fogging and Fumimentioning
confidence: 99%